Maternal knowledge, outcome expectancies and normative beliefs as determinants of cessation of exclusive breastfeeding: a cross-sectional study in rural Kenya. (December 2016) - Gewa, Constance; Chepkemboi, Joan
Abstract Background Despite the importance of multiple psychosocial factors on nutrition-related behavior, very few studies have explored beyond the role of mothers' knowledge and perception of child-focused outcomes on the duration of exclusive breastfeeding in Africa. Our objective was to determine the relationships among mothers' knowledge, outcome expectancies, normative beliefs, and cessation of exclusive breastfeeding in rural Kenya. Methods A cross-sectional survey was conducted among 400 mothers of children, 0-24 months old, in rural Kenya. Early child-feeding practices, knowledge of breastfeeding recommendations, beliefs associated with impact of exclusive breastfeeding on child- and mother-focused outcomes and perception of acceptability of exclusive breastfeeding by important others were examined. Cox regression analysis was used to assess the relationship between independent variables of interest and cessation of exclusive breastfeeding. Results Being knowledgeable of breastfeeding-related recommendations, positive beliefs on the impact of exclusive breastfeeding on child- focused outcomes, having a more positive perception of the impact of exclusive breastfeeding on mother-focused outcomes and a more positive perception of acceptability of exclusive breastfeeding by important others were associated with significantly lower risks of premature cessation of exclusive breastfeeding. Conclusion In addition to knowledge levels, mothers' beliefs play an important role in mothers' decisions to practice exclusive breastfeeding. Mother's beliefs on the impact of exclusive breastfeeding on the mother's health, physical appearance and ability to engage in other activities were shown to have the strongest relationship with premature cessation of exclusive breastfeeding. Addressing these beliefs has the potential to contribute to more effective exclusive breastfeeding promotion efforts in rural Kenya.